Critical Spirituality in Holistic Practice - Gardner, Fiona (Journal for the Study of Spirituality, 2016)
This paper is based on a keynote presentation given at the Annual Conference of the British Association for the Study of Spirituality in May 2016 which posed the question Can spirituality transform the world?'. Including the spiritual is an increasing expectation for those engaged in human service organisations, partly because of their work with those experiencing trauma and change and partly because of greater individual and community interest. Human service professionals currently wrestle with these expectations, often feeling undertrained and underprepared to undertake such practice. Critical spirituality is a framework influenced by research with health and social care professionals who wanted actively to include the spiritual in their professional practice. Critical spirituality means seeing people holistically, seeking to understand where they are coming from' and what matters to them at a fundamental level; the level that is part of the everyday but which also transcends it. This framework can be used to argue for the integration of the critical, the reflective and the spiritual into a coherent approach to practice that is holistic, inclusive and addresses issues of social justice. The expectation is to combine post-modern valuing of the diversity of individual and/or community spiritual experiences with a critical perspective that asserts the importance of living harmoniously and respectfully at an individual, family and community level. This framework generates both principles and strategies for transforming practice and, through practice, the world.